What is important in recovery from complex mental health difficulties? A research portfolio - Dunnett, Linsay Catharine (The University of Edinburgh, 2019)
Introduction and Aims: Recovery from severe and enduring mental health difficulties, such as psychosis, continues to be researched and is an area of importance regarding the development of successful interventions to help increase quality of life and wellbeing. Systematic Review – This aimed to review the current literature base regarding studies which have investigated change in self-compassion as an outcome measure, pre to post intervention, for individuals living with severe and enduring mental health difficulties. Empirical Study – Using a qualitative approach, this study was interested in investigating young people’s experiences of early psychosis. In particular, to investigate 1) the importance of autobiographical memories in young people’s recovery and 2) in what way early adverse experiences and memory formation affect future thinking and establishing an overall sense of self during this recovery process. Methodology: Systematic Review – Search terms were used within PsychInfo, Embase and Ovid databases in order to locate all papers which included a severe and enduring population and used compassion as an outcome pre and post an intervention. Fourteen studies were included for review. Quality was rated, using adaptations of the NICE and CASP checklists; two small meta analyses were also conducted in order to pool effect sizes. Empirical Study – Eight young people, from 16-19 years, were interviewed using a grounded theory approach. Interviews were transcribed and coded following each individual interview and developed over time; line by line coding was initially used, followed by the development of more focused codes and salient themes. This was combined with the completion of quantitative outcome measures in order to triangulate the data. Results: Systematic Review – Studies were grouped into two separate categories: those which had a control group and those which had a repeated measures design. Pooled effect sizes illustrated that self-compassion was shown to increase significantly in the intervention group in comparison to controls, and for groups over two time points. Studies are discussed separately, focusing on limitations, and then drawing on similar themes. Empirical Study – Salient categories which emerged from the interviews were: interpersonal connections, self-identity, choice and freedom, recovery and autobiographical memory. These are discussed in addition to sub-categories and with reference to quotes from young people. Locus of control was used to understand the findings, linking them to theory and models based in the literature. Conclusions: Systematic Review – The current review offers some support to the literature and suggests that self-compassion can be generated and increased in this population, who are susceptible to self-stigma and shame. The varied quality of studies, however, suggests a need for higher quality RCTs in order to increase our understanding and aid the development of more successful interventions for this complex population. Empirical Study – Findings illustrate the importance of helping young people develop coherent narratives of their experiences, in turn helping to build a sense of sense following early psychosis. Locus of control was found to be a helpful concept in viewing recovery and is helpful to consider when working with this population. Results from the current study were also shown to support literature in the area of positive contributions and empowerment, which are shown to be key for young people during recovery and will be helpful areas for further research.
Keywords: compassion; emotional systems; CBT; complex disorders; CFT; stigma; shame